Performance changes during the off-season period in football players – Effects of age and previous hamstring injury. Issue 21 (1st November 2020) - Vicens-Bordas, Jordi; Esteve, Ernest; Fort-Vanmeerhaeghe, Azahara; Casals, Martí; Bandholm, Thomas; Ishøi, Lasse; Opar, David; Shield, Anthony; Thorborg, Kristian
ABSTRACT: The aims of this study were to investigate changes in selected performance measures during an off-season period, their association, and the potential role of age and previous hamstring injury in semi-professional and amateur football players. Seventy-four male players (age: 25 ± 4 years, stature: 178.0 ± 6.6 cm, body mass: 74.9 ± 8.1 kg) were assessed at the beginning and end of the off-season summer-period for sprint, change-of-direction performance and eccentric hamstring strength. Small to medium increases in sprint times were observed at 5 (d = 0.26, p = 0.057), 10 (d = 0.42, p < 0.001) and 30 m (d = 0.64, p < 0.001). Small (d = −0.23, p = 0.033) improvements were observed for COD performance, and no changes in eccentric hamstring strength (d = 0.10, p = 0.317). The changes in the outcomes were not affected by age (p = 0.449 to 0.928) or previous hamstring injury (p = 0.109 to 0.995). The impaired sprint performance was not related to changes in eccentric hamstring strength (r = −0.21 to 0.03, p = 0.213 to 0.856), instead, changes in COD performance were associated with changes in eccentric hamstring strength (r = −0.42, p = 0.008).